Energy Drinks Induce Acute Cardiovascular and Metabolic Changes Pointing to Potential Risks for Young Adults: A Randomized Controlled Trial. Issue 3 (26th February 2019) - Basrai, Maryam; Schweinlin, Anna; Menzel, Juliane; Mielke, Hans; Weikert, Cornelia; Dusemund, Birgit; Putze, Kersten; Watzl, Bernhard; Lampen, Alfonso; Bischoff, Stephan C
ABSTRACT: Background: Case reports suggest a link between energy drinks (EDs) and adverse events, including deaths. Objectives: We examined cardiovascular and metabolic effects of EDs and mixtures providing relevant ingredients of EDs compared to a similarly composed control product (CP) without these components. Methods: This randomized, crossover trial comprised 38 adults (19 women, mean BMI 23 kg/m 2, mean age 22 y). We examined effects of a single administration of a commercial ED, the CP, and the CP supplemented with major ED-ingredients at the same concentrations as in the ED. The study products were administered at 2 volumes, 750 or 1000 mL. Results: Both volumes of the study products were acceptably tolerated with no dose-dependent effects on blood pressure (BP, primary outcome), heart rate, heart rate corrected duration of QT-segment in electrocardiography (QTc interval), and glucose metabolism. After ED consumption, 11% of the participants reported symptoms, in contrast to 0–3% caused by other study products. After 1 h, administration of an ED caused an increase in systolic BP (116.9 ± 10.4 to 120.7 ± 10.7 mmHg, mean ± SD, P  < 0.01) and a QTc prolongation (393.3 ± 20.6 to 400.8 ± 24.1 ms, P  < 0.01). Also caffeine, but not taurine or glucuronolactone, caused an increase in BP, but no QTc prolongation. The BP effects were most pronounced after 1 h and returned to normal after a few hours. All study products caused a decrease in serum glucose and an increase in insulin concentrations after 1 h compared to baseline values, corresponding to an elevation in the HOMA-IR (ED + 4.0, other products + 1.0–2.8, all P  < 0.001). Conclusion: A single high-volume intake of ED caused adverse changes in BP, QTc, and insulin sensitivity in young, healthy individuals. These effects of EDs cannot be easily attributed to the single components caffeine, taurine, or glucuronolactone. This trial was registered at clinicaltrials.gov as NCT01421979.